Roberts & Zuckerman's Criminal Evidence - Roberts, Paul (Oxford scholarship online, 2022)
Roberts & Zuckerman's Criminal Evidence gives an authoritative commentary on the fundamental principles and underlying logic of criminal evidence laws. It also tackles the foundations of principles for a fair trial, the presumption of innocence, the privilege against self-incrimination, and bad character evidence while engaging with the broader jurisprudential, moral, and political significance of evidence rules. Major doctrinal developments on evidence changes and cases are addressed such as cases relating to confession evidence, torture evidence, reverse onus clauses, confrontation, hearsay, previous sexual history, and bad character evidence. The title also includes the forensic applications of inductive logic, narrative, and probability.